One-step synthesis and characterization of reduced graphene oxide using chemical exfoliation method. (June 2019) - Gebreegziabher, G.G.; Asemahegne, A.S.; Ayele, D.W.; Dhakshnamoorthy, M.; Kumar, A.
Abstract: Graphene has many potential applications. Currently, its synthesis starts with the oxidation of graphite to graphene oxide followed by a separate reduction step. But, this leads to extra cost, prolonged time, and contamination. Here, we report the preparation of reduced graphene oxide (rGO) directly from graphite in a solution of potassium permanganate and concentrated sulfuric acid assisted by ultrasonication. The morphology, optical, chemical, thermal, microstructural, and electrical properties of prepared samples were studied using scanning transmission electron microscopy, selected area electron diffraction, ultra violet-visible spectroscopy, Fourier-transform infrared spectroscopy, thermogravimetric analysis, Raman spectroscopy, X-ray powder diffraction, and cyclic voltammeter, respectively. The analysis confirms that quality of rGO with thickness (∼0.36 nm) that can be dispersed in water with the desired properties was obtained. We can use this method to prepare rGO directly from graphite for energy storage. Graphical abstract: Image 1 Highlights: Synthesis of reduced graphene oxide (rGO) from graphite without separate reduction procedure. Morphological and microstructure properties of rGO were characterized using scanning transmission electron microscopy (STEM), X-ray powder diffraction, and Raman spectroscopy. Electrochemical stability and chemical properties of rGO were analyzed using cyclic voltammeter and Fourier-transform infrared spectroscopy. Few-layer rGO with reasonable amount of oxygen and lower defects is prepared.